Gejala Primer Serangan Stroke pada Pasien Dengan Serang Pertama - Agung, Rizki Nugraha; Jumaiyah, Wati; Siswandi, Iyar; Rinawati, Rinawati; Jum’atina, Jum’atina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to identify stroke symptoms that often occur in first-attack stroke patients. Using observational method with secondary data from medical records of stroke patients. The results of the study showed that the symptoms of stroke that often occurred in first stroke stroke patients were experiencing sudden weakness in the movement of half of the body (hands and feet) as many as 89 people (96.08%). Then, the majority of stroke patients had a history of disease, namely hypertension, 88 people (86.3%). and The majority of stroke onset when patients arrived at the hospital in this study was more than 3.5 hours but still under 24 hours. 63 people (61.8%). The conclusion from this study can be seen that the majority of the main symptoms of a stroke are experiencing sudden weakness in the movement of one side of the body (hands and feet) with the onset of stroke when the patient arrives at the hospital in the majority more than 3.5 hours but still less than 24 hours. Keywords: Hypertension, Stroke, Stroke onset, Stroke symptoms